2020
DOI: 10.1029/2020gl087837
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Electrostatic Waves Associated With Turbulent Plasma Mixing in the Kelvin‐Helmholtz Instability

Abstract: The Kelvin‐Helmholtz Instability (KHI) is thought to be an important driver of mass and momentum transfer from the solar wind to the Earth's magnetosphere. We present observations from NASA's Magnetospheric Multiscale mission of ion acoustic‐like waves associated with turbulence during the KHI interval on 8 September 2015. These parallel electrostatic waves are nonlinear, can have amplitudes in excess of 100 mV/m, and may be associated with a field‐aligned potential drop. We perform a survey of all vortices in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
(72 reference statements)
3
7
1
Order By: Relevance
“…This is consistent with observations of the reconnecting dayside magnetopause, where the bulk of the plasma wave activity occurred on the magnetospheric side of the current sheet (Wilder et al, 2019). It is also similar to the Ion Acoustic Waves (IAWs) observed in the KHI by (Wilder et al, 2020), which seemed to occur on the magnetospheric side of the "vortex" intervals, though in that case, the waves occurred closer to B Y 0, in a region referred to as the "turbulent mixing region. "…”
Section: Solitary Wave Detector Statisticssupporting
confidence: 88%
See 3 more Smart Citations
“…This is consistent with observations of the reconnecting dayside magnetopause, where the bulk of the plasma wave activity occurred on the magnetospheric side of the current sheet (Wilder et al, 2019). It is also similar to the Ion Acoustic Waves (IAWs) observed in the KHI by (Wilder et al, 2020), which seemed to occur on the magnetospheric side of the "vortex" intervals, though in that case, the waves occurred closer to B Y 0, in a region referred to as the "turbulent mixing region. "…”
Section: Solitary Wave Detector Statisticssupporting
confidence: 88%
“…This was the first KHI interval observed by MMS with enough periods to do statistical analysis of the instability. Previous studies of this event have shown magnetic reconnection on compressed current sheets (Eriksson et al, 2016a;Eriksson et al, 2016b), turbulence in the vortex-like intervals between the current sheets (Stawarz et al, 2016), and large-amplitude ion-acoustic waves in the plasma mixing regions on the magnetospheric side of the vortex-like intervals (Wilder et al, 2016a;Wilder et al, 2020).…”
Section: The 8 September 2015 Kelvin-helmholtz Eventmentioning
confidence: 82%
See 2 more Smart Citations
“…Notably, the mixing of the boundary layer and magnetosheath plasma populations within the vortices can lead to complex particle distribution functions and kinetic instabilities. Such behavior has been noted in particular through the examination of high-frequency electric field activity in the 8 September 2015 KHI (Wilder et al 2016(Wilder et al , 2020. Vortex-induced reconnection events are also know to be set up by the large-scale configuration of the system, both at mid-latitudes associated with twisted field lines above and below the KH vortices and at the compressed current sheets between the vortices (e.g., Nykyri & Otto 2001;Faganello et al 2012;Nakamura et al 2013;Eriksson et al 2016a;Vernisse et al 2016).…”
Section: Discussionmentioning
confidence: 92%